2016
DOI: 10.1039/c5sc02319j
|View full text |Cite
|
Sign up to set email alerts
|

Surface water retardation around single-chain polymeric nanoparticles: critical for catalytic function?

Abstract: A library of water-soluble dynamic single-chain polymeric nanoparticles (SCPN) was prepared using a controlled radical polymerisation technique followed by the introduction of functional groups, including probes at targeted positions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 37 publications
1
43
0
1
Order By: Relevance
“…Further, the helicity of these internal domains can be tuned based on the chirality of the alkyl side chains of the BTA units . These complex internal domains have further been used to design a broad array of SCNPs, which are catalytically active in water …”
Section: Architecture Beyond Intramolecular Crosslinksmentioning
confidence: 99%
“…Further, the helicity of these internal domains can be tuned based on the chirality of the alkyl side chains of the BTA units . These complex internal domains have further been used to design a broad array of SCNPs, which are catalytically active in water …”
Section: Architecture Beyond Intramolecular Crosslinksmentioning
confidence: 99%
“…Research has shown that hetero‐dimers using a Thymine‐diaminopyridine, or a Hamilton wedge‐cyanuric acid combination can be utilized for SCNP formation. In addition, self‐complementary systems can also be used, in particular 2‐Ureido‐4[1H]‐pyrimidinone (UPy) quadrupule hydrogen bonding dimerization, and Benzene‐1,3,5‐tricarboxamide (BTA) self‐assembly . BTAs show significant advantage for this purpose as they exhibit threefold hydrogen bonding and stacking that results in helical structures.…”
Section: Protein‐like Structurementioning
confidence: 99%
“…Using a suite of SCNP with varying functionality (Fig. ), the group probed BTA‐PEG‐TEMPO, hexadecyl‐PEG‐TEMPO, and unfunctionalized‐PEG‐TEMPO polymers using electron paramagnetic resonance (EPR) and Overhauser dynamic nuclear polarization (ODNP) NMR relaxometry . They discovered that using the surface water diffusivity at the surface of the SCNP is the only experimental signature that, when probed, gives any insight into the local environment around a folded and unfolded SCNP.…”
Section: Protein‐like Functionmentioning
confidence: 99%
“…27 Recently, Overhauser dynamic nuclear polarization NMR has been employed to investigate the local water translational diffusion dynamics at the site where catalysis would occur. 28 All these experiments have provided detailed information on the properties of SCPNs and the factors that may affect their catalytic performance. While these approaches were mostly focused on structural aspects, methods that are able to directly monitor the catalytic reaction are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] A number of techniques have been employed to investigate the BTA-based SCPNs and to improve our understanding of how their 3D structures relate to their functions. [25][26][27][28] Circular dichroism (CD) spectroscopy and scattering techniques have been utilized to study their inner structure and shape; 25,26 single-molecule force spectroscopy has been introduced to provide information on the folding kinetics and pathways. 27 Recently, Overhauser dynamic nuclear polarization NMR has been employed to investigate the local water translational diffusion dynamics at the site where catalysis would occur.…”
Section: Introductionmentioning
confidence: 99%